Exploring the Use of Tweets and Word Clouds as Strategies in Educational Research - Dorothy Cooshna-Naik (Journal of Learning for Development, 2022)
This paper presents personal insights and discussions on the exploration of specific strategies which relate to data collection and analysis used to support the focus group discussion data collection and preliminary analysis of a doctoral research entitled Undergraduate students’ experiences of learning with digital multimodal texts. The main objective of the doctoral research was to understand the different ways undergraduate students experienced learning with digital multimodal texts (DMTs) within the context of a history module included in their first-year programme of studies both as readers (consumers) and authors (producers). Data were collected through semi-structured interviews, written reflection accounts, a focus group discussion and consideration given to the DMT (a video) produced by the participants. The focus group discussion event included a hands-on task whereby participants were requested to write their views in response to a given prompt question in the form of tweets. Also, the written tweets were visualised as word clouds for the purpose of initial analysis. The findings reported in this paper, which are based on observation notes and investigation of the word clouds, suggest that the tweet-related, hands-on task acted as a good ice breaker, making the participants feel at ease and more relaxed about sharing their views amongst each other while eliciting discussions and fostering deeper thinking. Also, the word clouds were revealed to be an effective data visualisation tool allowing emerging and salient themes to stand out from the participants’ written tweets and reflections.